External invasive resorption: Case report of a rapidly progressive process in an impacted maxillary canine during orthodontic treatment. (16th August 2018) - Shemesh, Avi; Birnboim‐Blau, Galit; Zoizner, Ronen; Itzhak, Joe Ben; Solomonov, Michael
Abstract: External invasive resorption (EIR) is a type of external resorption that can involve the coronal, middle and apical parts of the root in its advanced stages and results in progressive loss of tooth structure. Common potential predisposing factors for EIR are orthodontic treatment and trauma. The EIR progression rate has not been described previously. This case report describes rapidly progressive EIR in an impacted maxillary canine after surgical exposure and application of directional orthodontic traction over 8 months. The article discusses the etiologies of EIR, the possible reasons for EIR and its rapid progression in the presented case and proposes a new theory of the connection between EIR and tooth impaction.